Infrared spectroscopy investigation of various plasma-deposited polymer films irradiated with 170 keV He+ ions - Gelamo, R. V.; Trasferetti, B. C.; Durrant, S. F.; Davanzo, C. U.; Rouxinol, F. P.; Gadioli, G. Z.; Bica de Moraes, M. A. (Elsevier B.V., 2006)
This work illustrates the advantages of using p-polarized radiation at an incidence angle of 70 degrees in contrast to the conventional unpolarized beam at normal (or near-normal) incidence for the infrared spectroscopic study of polycarbosilane, polysilazane and polysiloxane thin films synthesized by plasma enhanced chemical vapor deposition (PECVD) and subsequently irradiated with 170 keV He+ ions at fluences from 1 x 10(14) to 1 x 10(16) cm(-2). Several bands not seen using the conventional mode could be observed in the polarized mode. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ion irradiation; Si-based polymer film; plasma polymerization; chemical structure; FTIR